The Impact of Corporate Culture, Competence, and Remuneration on Job Satisfaction and Its Implications for Employee Performance: Evidence from PT Aplikanusa Lintasarta - Ariyanto, Antonius Sapto (Priviet Social Sciences Journal, 2022)
This study aims to examine the influence of corporate culture, competence, and remuneration on job satisfaction and their impact on employee performance at PT. Aplikanusa Lintasarta. The research adopts a quantitative approach using a survey method, where primary data were collected through structured questionnaires distributed to employees. A total of 88 valid responses were analyzed using descriptive statistics and path analysis to evaluate both direct and indirect relationships among variables. The results indicate that corporate culture and remuneration have a significant positive effect on job satisfaction, while competence does not significantly influence job satisfaction. Remuneration is identified as the most dominant factor affecting job satisfaction. Furthermore, competence and corporate culture are found to have significant direct effects on employee performance, with competence being the most influential variable. In contrast, remuneration and job satisfaction do not have a significant direct impact on employee performance. Additionally, job satisfaction does not act as a strong mediating variable between independent variables and performance. These findings suggest that employee performance is primarily driven by competence and supported by a strong organizational culture, whereas remuneration mainly influences employees’ level of satisfaction rather than performance outcomes. The study highlights the importance of aligning human resource strategies, particularly in enhancing employee competence and strengthening organizational culture, while also improving compensation systems to increase job satisfaction